Effect of feeding Black soldier fly larvae (BSFL) on the quail performance in Kelantan - Nur Amira Shakila Mohamad (2016)
This study was carried out to determine effect of feeding three different percentage of Black Soldier Fly Larvae (BSFL) in commercial feed on the growth performance of quail. Besides that, this research also want to identify the laying performance on the quail that feeding the three different percentage of Black Soldier Fly Larvae (BSFL) in commercial feed also identify the feed efficiency of the quail that provided with BSFL in the commercial feed and without the BSFL. 48 of Japanese quail reared and divided into four group with different ration of BSFL in diet. The group was dividing into quail that provide 25%BSFL with commercial feed, 20%BSFL with commercial feed, 15%BSFL with commercial feed and the quail that consume commercial feed only. The performance of quail was determined by observed the growth and laying performance that included measure the feed intake, body weight gain, feed conversion ratio (FCR), growth rate, also calculating the egg shell thickness, egg weight and total egg count. From this research, the result shows that the hypothesis of this experiment was accepted as all of the result shows signiﬁcantly (p<0.05) effect to the quail performance when comparing them between the treatment except in the egg quail production and eggshell thickness. This research noted the p value for feed consumption, feed conversion ratio, growth rate, body weight gain, and egg weight is 0.001, 0.002, 0.000, 0.000, and 0.000 respectively. While the p value for egg production and egg shell thickness is 0.124 and 0.211 respectively. Although it not signiﬁcant (p>0.05) in the result but it still shows better performance in quail that provide BSFL in diet compare to the quail that provided with commercial feed only. In addition, the quail that consume with 25% of BSFL in the diet was lead all of the result. Hence, it shows better performance in growth and laying production compare to the other. The ratio of 25% BSFL with the commercial feed can be concluded as a better ration compare other and can be supply to the quail for making improvement of their performance. BSFL also can be assuming as a better supplement feed to the quail as it shows positive results in this research.